The CORRELATION SPICY SNACK CONSUMPTION AND DIGESTIVE SYSTEM DISORDERS IN CHILDREN IN NGUMPUL VILLAGE, JOGOROTO DISTRICT, JOMBANG REGENCY - Ruliati Ruliati; Siti Shofiyah (STIKES Insan Cendekia Medika Jombang, 2026)
Introduction Spicy foods can be the main trigger for digestive system disorders in children and adolescents. Digestive system disorders with pain symptoms can cause nutritional problems in children and adolescents such as anemia. The objective presence of cases of digestive system disorders in children can affect their quality of life. The aim is to determine the consumption of spicy snacks with digestive system disorders in children in Ngumpul Village, Jogoroto District, Jombang Regency.. Method. This study used an analytic survey with a cross-sectional approach. The research was conducted from March 2025 to January 2026. The sample size for this study was 60 individuals, selected using purposive sampling. Data analysis was performed using the chi-square test (p-value<0.05). Result The study showed that out of 60 respondents, 11 (18%) respondents consumed spicy snacks every day, of the 11 respondents, 9 (15%) experienced digestive system disorders. 37 respondents (62%) consumed spicy snacks more than 3 times a week, of the 37 respondents, 11 (18%) respondents experienced digestive system disorders. 26 (44%) respondents did not experience digestive system disorders. The results of the chi-square test obtained a p value of 0.013 so it is smaller than α (0.05).Conclution The research findings indicate a relationship between spicy eating consumtions and an digestive system disorders in children in Ngumpul Village, Jogoroto. It is expected that parents will be more selective in providing snacks to their children, and health workers will provide education to Parents and children should reduce eating spicy snacks, Keywords: Digestive system disorders, Spicy snacks, Consumption, Child